A questão da diluição da dignidade humana a partir do pensamento de Hannah Arendt - Giovanelli, Silio (2018)
This dissertation intends to deal with the relations of individuals in the domains of human actions based on Arendtian thought. We realize that the dilution of the dignity of those individuals who are willing to make their appearance in these spaces is increasingly common, but is not, however, something unique or exclusive to the experience of our contemporary society. What causes us strangeness most is how such practices have become banal, common, often arising in futile, clumsy motives, without even encountering an obstacle in height. Studying the works of Hannah Arendt, we will seek to list, from her analysis of the Human Condition, the possible motives for the banal practice of such acts. We will seek to highlight the need to distinguish concepts so that one can assume respect for the person of the other and their dignity as such in the spaces of coexistence to which we come. In this way, we will investigate the distinctive characteristics of the concepts of Public and Private as well as of the concepts of Labor and Work, making the problem of the emergence of the social domain and mass society second, the issue of productivity and unproductivity related to the actions carried out, finally analyzing the problematic issue of consumer societies. Finally, we will analyze the concept of Action seeking to highlight the character of human thought as the primordial activity of human life, presenting this activity as a possible way of coping with the problem of the dilution of the Human Dignity, assuming for this purpose the question of reciprocity and otherness in the relationships of individuals towards others that coexist with the domains of human affairs.